An attenuated replication-competent chikungunya virus with a fluorescently tagged envelope. - Jing Jin; Michael B Sherman; Daniel Chafets; Nuntana Dinglasan; Kai Lu; Tzong-Hae Lee; Lars-Anders Carlson; Marcus O Muench; Graham Simmons (Public Library of Science (PLoS), 2018)
BACKGROUND:Chikungunya virus (CHIKV) is the most common alphavirus infecting humans worldwide, causing acute and chronically debilitating arthralgia at a great economic expense. METHODOLOGY/PRINCIPAL FINDINGS:To facilitate our study of CHIKV, we generated a mCherry tagged replication-competent chimeric virus, CHIKV 37997-mCherry. Single particle cryoEM demonstrated icosahedral organization of the chimeric virus and the display of mCherry proteins on virus surface. CHIKV 37997-mCherry is attenuated in both IFNαR knockout and wild-type mice. Strong anti-CHIKV and anti-mCherry antibody responses were induced in CHIKV 37997-mCherry infected mice. CONCLUSIONS/SIGNIFICANCE:Our work suggests that chimeric alphaviruses displaying foreign antigen can serve as vaccines against both aphaviruses and other pathogens and diseases.